Digital Rhetoric and Algorithmic Ethics: A Literature Review of Digital Communication - Ibrahim, Riza Andrian; Lianingsih, Nestia (Communication In Research And Publications, 2025)
In the digital age, communication has become increasingly shaped by algorithmic systems that structure interaction, visibility, and persuasion across online platforms. This literature review explores the convergence of digital rhetoric and algorithmic ethics to understand how meaning-making and moral agency are co-constructed in contemporary digital environments. Digital rhetoric, concerned with how persuasion operates in multimodal and interactive contexts, now intersects with algorithmic processes that govern content distribution and user engagement. Simultaneously, the rise of algorithmic ethics addresses the sociotechnical implications of bias, opacity, and accountability embedded in machine-driven communication infrastructures. Through a qualitative synthesis of recent scholarship, this study identifies four core themes: algorithmic persuasion, content visibility and bias, platform governance, and ethical resistance. The findings show that algorithms are no longer neutral tools but rhetorical actors that influence how narratives are constructed and circulated. Moreover, the literature highlights growing concerns about fairness, transparency, and user autonomy, especially in the realms of political discourse, media consumption, and educational technologies. The study concludes that navigating digital communication today demands both rhetorical literacy and ethical sensitivity. A deeper understanding of how algorithmic systems persuade, exclude, or amplify certain voices is vital for promoting equitable and informed public discourse. This review contributes to a critical framework that connects digital rhetoric and algorithmic ethics, offering insights into the rhetorical and moral complexities of our algorithmically mediated world.